Hubungan Antara Pola Asuh Demokratis Terhadap Kemandirian Anak Di Kota Bengkulu - Putri, Rizki Yunita (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2021)
Parenting patterns are very important and affect the independence of children, person's childhood experiences greatly affect the development of a child's personality in the future, including his character or emotional intelligence. In Group B, Shandy Putra Telkom Kindergarten students in Bengkulu City come from different family backgrounds, some from civil servants, doctors, private workers, TNI, farmers, traders, and many more, from families with different backgrounds. Each family has a unique upbringing, has a different parenting pattern in each family. The main problem in this study is the relationship between Democratic Parenting Patterns on Children's Independence in Group B TK Shandy Putra Telkom Bengkulu City. Is there a relationship between democratic parenting and the independence of early childhood in Group B TK Shandy Putra Telkom Bengkulu City. This research is a quantitative research type of correlational research, namely research conducted to determine the relationship between two or more variables. Data collection procedures or techniques in this study are used to collect data by using tools/instruments to obtain data and information expected from respondents. in this study is a questionnaire. From the research, it can be concluded that there is a positive and significant relationship between democratic parenting and the independence of children in group B of Shandy Putra Telkom Kindergarten, Bengkulu City